Narrativa do processo da minha formação médica - Agudelo, Jhon Aanderson Bonilla (Universidade Federal de São Carlos, 2020)
This Course Conclusion Paper will be prepared in accordance with the guidelines of the Pedagogical Project of the UFSCar Medicine Course. O CBT will have a critical-reflective narrative about my education, with emphasis on professional practice, the same separated into five places main ones, the first will address the impact emitted upon arrival at the university, the following will deal chronologically with the three cycles, from which the pedagogical structure of the medical course is organized and the fifth will deal with extracurricular activities developed during my training.
Narrative of the process of my medical training
Keywords: Narrativa; CIENCIAS HUMANAS::EDUCACAO::ORIENTACAO E ACONSELHAMENTO::ORIENTACAO EDUCACIONAL